Melanoma metastasis to the oral cavity: a rare case report and literature review - Sandra Baranovic; Aleksandar Milenovic (Journal of Clinical and Investigative Surgery, 2022)
About 1% of oral cancers are metastases of primary tumors from other parts of the body. The most common primary tumors that metastasize to the oral cavity are placed in the lungs, kidneys, liver and prostate for men, while in women they are placed in the breasts, genital organs, kidneys and colon. The oral cavity is an unusual place for the metastatic spread of primary tumors, especially malignant melanoma, and is usually a sign of the widespread dissemination of the malignancy. When they occur, oral metastases are most often found in the jawbones. Most of the reported soft tissue oral melanoma metastases were localized in the tongue. We report a case of a 50-year-old female patient with a melanoma metastasis in the floor of the oral cavity. The treatment chosen was the transoral excision of the metastatic tumor of the mandibular mucosa and floor of the mouth. We chose this option primarily to relieve the patient's symptoms, so the therapeutic indication was palliative.